The Reception of the Qur'an in Popular Orders in West Java: A Living Quran Study Between Local Rituals and Traditions : Resepsi Al-Qur’an pada Tarekat-Tarekat Populer di Jawa Barat: Studi Living Quran Antara Ritual dan Tradisi Lokal - Hambali , R. Yuli Ahmad; Solehudin (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This research is motivated by the phenomenon of Living Qur'an in the community of tariqat in West Java, which shows that the acceptance of the Qur'an is not limited to textual interpretation, but is also manifested in the form of rituals and spiritual practices rooted in local traditions. The purpose of this study is to describe the pattern of reception of Qur'anic verses in three popular institutes, namely Tijaniyah, Qadiriyah, and Qadiriyah wa Naqsyabandiyah, as well as to examine the interaction between sacred texts and Sundanese cultural traditions in daily life. This study uses a qualitative approach with a descriptive-analytical method, through field observations, in-depth interviews, and documentation studies on the religious practices of the tarekat community in three districts: Garut, Cianjur, and Tasikmalaya. The results of the study show that each tarekat has a typical pattern of reception of the Qur'an in the form of wirid, prayer, dhikr, and ritual processions such as tawasul, istighatsah, manaqib, haul, and tanbih. Local traditions, such as ngabungbang, Friday night Kliwon, and haul commemorations, also influence the form and meaning of these religious rituals. The conclusion of this study is that the verses of the Qur'an live in the spiritual praxis of the tarekat community through the integration of religious texts and local cultures. The novelty of this research lies in the contextual analysis of the interaction of the reception of the Qur'an with local cultural expressions in three tariqat at once, which has not been widely explained in the study of Living Qur'an in Indonesia.